Evaluating the Efficacy of COVID-19 Vaccines in Reducing Infection and Symptomatic Presentation in Libya - Najat M. Al- Ghatmi; Hosni A- Dawadi; Ali Dow; Kunouz Quraysiah; Amani Ziada (African Journal of Advanced Pure and Applied Sciences, 2026)
Vaccination against SARS-CoV-2 remains the primary global strategy to mitigate the pandemic and reduce viral contamination and transmission. Despite full vaccination, breakthrough infections can still occur, as evidenced by international clinical data. This study aimed to evaluate the effectiveness of COVID-19 vaccines in preventing infection and reducing the severity of symptoms among Libyan citizens. A cross-sectional survey was conducted between September 2021 to February 2022, collecting data from 1,183 vaccinated and 275 unvaccinated individuals. The results showed an infection rate of 10.4% among the vaccinated group compared to 25.4% in the unvaccinated control group. Statistically significant differences were observed in both infection rates and symptom severity between the two groups. Furthermore, household contact with infected family members was identified as the most prevalent source of infection among vaccinated participants.